Weight gain of Progestin and Combined Contraceptive Users - Tinuk Esti Handayani; Agung Suharto (Health Notions, 2018)
Background: Family planning was one of the efforts for achieving prosperity by providing advice on marriage, infertility treatment, and birth spacing. The Family Planning Method of injectionhad become part of National Family Planning Movement and its interest grew more and more. The purpose of this research was in order to know the influence between the use of Family Planning of progestin injection and combination injection against weight gain. Methods: This type of research was analytical research with case control design. The populations of this research were Family Planning acceptor who had progestin injection and combination injection at Public Health Center of Poned Panekan, Magetan, Indonesia. The samples were 210 people by cluster random sampling technique. Data analysis utilized Paired T-Test and Linear Regression with probability 0.05. Results: Paired TTest analysis result was obtained p = 0.000 (<0.05), which meant that there was a significant difference between body weight before and after. The result of linear regression analysis showed that there was a significant influence between age and body weight before, which had p = 0.000 (p <0.05), body weight after in Family Planning, which had p = 0.000 (p <0.05), and no long-term effect of Family Planning to body weight after, which had p = 0.58 (p> 0.05). Conclusion: there was a significant influence between age and Family Planning of injection against the acceptor’s weight gain.Moreover, the progestin injection acceptor’s weight gain was greater rather than combination injection acceptor.Keywords: Weight gain, Progestin cntraceptive, Combine contraceptive